Developing Digital Media on Teaching Writing Descriptive Text Using Doratoon for Seventh Grade Students at MTSS Al-Washliyah Senayan Kec. Sei Rampah - Nurhasanah; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2025)
This study focuses on how digital media on teaching writing descriptive text are developed for junior high school. The study is aimed to develop a doratoon as digital media to teaching writing descriptive text for seventh grade students at MTSS Al-Washliyah Senayan, Kec. Sei Rampah. This research applied the Borg and Gall (2003) with some modifications, which was simplified into six stages to shorten time and cost. The data were obtained through an interview with an English teacher and distributing questionnaire to thirty students to get the students' needs analysis. Thirty students from clas7.1 served as the source of data. The findings revealed that both the interview and questionnaire results indicate that students need English teaching media that can motivate and interest them to understand descriptive text writing. The digital teaching media was validated by a lecturer from English education department and an English teacher from MTSS Al-Washliyah Senayan. The final product's result was videos containing audio-visual media to be used in teaching descriptive text writing. The result of the experts' validation showed that the media was an appropriate media to be used in teaching writing descriptive text by getting the average score percentage of 84% categorized as very good.